2014
DOI: 10.1051/0004-6361/201322856
|View full text |Cite
|
Sign up to set email alerts
|

Variability of massive stars with known spectral types in the Small Magellanic Cloud using 8 years of OGLE-III data

Abstract: We present a variability study of 4646 massive stars in the Small Magellanic Cloud (SMC) with known spectral types from the catalog of Bonanos et al. (2010) using the light curves from the OGLE-III database. The goal is to exploit the time domain information available through OGLE-III to gain insight into the processes that govern the evolution of massive stars. This variability survey of massive stars with known spectral types is larger than any previous survey by a factor of 7. We find that 60% of our sample… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 80 publications
2
37
0
Order By: Relevance
“…We distinguished 4 modes of variability similar to the modes presented in Keller et al (2002) for classifying the blue variables in the LMC, that consist of high-amplitude, long-term outbursts ("bumper" events), short-term and low-amplitude, sudden outbursts ("flicker" events), monotonic trends across the 8-year time domain ("monotonic") and decline of magnitude that lasts up to 1000 days ("fading" events) (see Fig. 9, Kourniotis et al 2014). Of our 443 irregular variables, ∼76% are newly reported as variables in the present work.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…We distinguished 4 modes of variability similar to the modes presented in Keller et al (2002) for classifying the blue variables in the LMC, that consist of high-amplitude, long-term outbursts ("bumper" events), short-term and low-amplitude, sudden outbursts ("flicker" events), monotonic trends across the 8-year time domain ("monotonic") and decline of magnitude that lasts up to 1000 days ("fading" events) (see Fig. 9, Kourniotis et al 2014). Of our 443 irregular variables, ∼76% are newly reported as variables in the present work.…”
Section: Resultssupporting
confidence: 57%
“…We then flagged variables as "periodic with extra variability" when their periodic signal varies in amplitude or baseline by more than 0.05 mag (see Fig. 8, Kourniotis et al 2014). The remaining periodic variables consist of 126 classical Cepheids and 50 stars flagged as "rotating variables" being sinusoidally periodic variables with unequal minima which implies a strong indication of tidal distortion effects for an ellipsoidal star or starspot modulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data appear significantly variable (the star was in fact reported as an "irregular variable" by Kourniotis et al 2014); a clear long-term modulation is readily detected by eye in OGLE data (Fig. 1).…”
Section: Dfs 936mentioning
confidence: 97%
“…Kourniotis et al 2014). Szczygieł et al (2010) showed that the majority of the identified variable massive stars in the LMC are RSGs, while the RSGs and AGB stars in M 33 have been the subject of variability studies in the near-IR (Javadi et al 2011) andmid-IR (McQuinn et al 2007).…”
Section: Variabilitymentioning
confidence: 99%